Magnetic resonance imaging in the evaluation of the stress system in acute and chronic cardiac disease - Markousis-Mavrogenis, George; Bacopoulou, Flora; Chrousos, George P.; Mavrogeni, Sophie I. (Diagnostics, 2025)
Various cardiac pathologies such as ischemic/non-ischemic heart disease, valvular heart disease and genetic heart disease may impair cardiac function and lead to heart failure (HF). Each individual condition but also the common endpoint of HF may involve the brain and the immune system next to the heart. The interaction of these systems plays an important role, particularly in the pathogenesis and prognosis of HF, and stress plays a pivotal role in this interaction. The stress system (SS) of the body can be activated by any stress factor exceeding a predefined threshold and all body structures including brain, heart and immune system can be affected. The SS is also responsible for body homeostasis. Both acute and chronic stress may lead to the development of acute and chronic heart disease. Magnetic Resonance Imaging (MRI) is the ideal noninvasive tool without radiation that can provide valuable information about the effect of the SS in various systems/organs using targeted protocols. A holistic approach provided by MRI has the potential to improve our knowledge regarding stress mechanisms on the axis of heart-brain-immune system in HF that may impact effective, individualized treatment. In this review paper, we describe how MRI can be used as a noninvasive tool to assess the effect of stress on the brain-immune system-heart-axis, discussing current possibilities, limitations and future directions.